Implementasi Manajemen Talenta untuk Regenerasi Pengrajin Batik di Desa Giriloyo - Putra, Okka Adittio; Sitanggang, Victor Rezeki Putra; Arista, Annisa; Maharani, Despita; Hartika, Mira; Sholehah, Sindy Mardianti; Utami, Tarin Dia; Hermawan, Dedy (Jurnal Pengabdian, 2025)
This community service program aims to support the regeneration of batik artisans in Giriloyo Village through a talent management approach. The activity was carried out using a participatory method that included identifying youth potential, assessing competencies, experiential-based training, and continuous mentoring. The training materials covered batik-making techniques, motif design based on local wisdom, digital marketing, and community leadership. The results showed a significant improvement in participants' technical skills and cultural understanding. Young participants became actively involved in batik production and promotion and established positive collaborations with senior artisans. The program also encouraged the emergence of creative youth communities and raised awareness of the importance of preserving local cultural heritage. This activity demonstrates that a talent-based human resource management strategy can offer effective solutions to regeneration challenges in traditional cultural sectors. Although constraints such as limited facilities and funding remain, the program has made a tangible contribution to strengthening the local creative economy and preserving intangible cultural heritage.